1999
DOI: 10.1097/00004728-199911000-00026
|View full text |Cite
|
Sign up to set email alerts
|

The Cervical Aortic Arch with Aneurysm Formation

Abstract: An asymptomatic 59-year-old man was admitted with an initial suspicion of mediastinal tumor. He was diagnosed as having a left-sided cervical aortic arch (Haughton type D) with arch aneurysm by using contrast-enhanced CT and angiography. The arch aneurysm was surgically removed. This is the 20th reported case of cervical aortic arch with aneurysm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Recent researches suggest that a cervical aortic arch is associated with deletions in chromosome 22q11, and hence these lesions could be included in the spectrum of defects known as catch 22. This syndrome, described by Wilson and colleagues in 1993, is characterized by cardiac defects, facial dysmorphic, thymic hypoplasia, cleft palate, hypocalcaemia, and a deletion in chromosome 22 [6,7]. For our patient the decision to proceed to the intervention was made on the combination of cervical aortic arch, pseudocoarctation and the presence of saccular aneurysms, even if the patient was asymptomatic.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent researches suggest that a cervical aortic arch is associated with deletions in chromosome 22q11, and hence these lesions could be included in the spectrum of defects known as catch 22. This syndrome, described by Wilson and colleagues in 1993, is characterized by cardiac defects, facial dysmorphic, thymic hypoplasia, cleft palate, hypocalcaemia, and a deletion in chromosome 22 [6,7]. For our patient the decision to proceed to the intervention was made on the combination of cervical aortic arch, pseudocoarctation and the presence of saccular aneurysms, even if the patient was asymptomatic.…”
Section: Discussionmentioning
confidence: 98%
“…A cervical aortic arch develops most likely from the persistence of the third branchial arch and is complicated by aneurysm in 20% of cases [4]. Cervical aortic arch may be symptomatic; and can be revealed by chest pain [5], oppression in the neck and dizziness, but are usually asymptomatic cases [6]. Recent researches suggest that a cervical aortic arch is associated with deletions in chromosome 22q11, and hence these lesions could be included in the spectrum of defects known as catch 22.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches suggest that a cervical aortic arch is associated with deletions in chromosome 22q11, and hence these lesions could be included in the spectrum of defects known as catch 22. This syndrome, described by Wilson and colleagues in 1993, is characterized by cardiac defects, facial dysmorphic, thymic hypoplasia, cleft palate, hypocalcaemia, and a deletion in chromosome 22 [6, 7]. For our patient the decision to proceed to the intervention was made on the combination of cervical aortic arch, pseudocoarctation and the presence of saccular aneurysms, even if the patient was asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Tsukamoto et al described repair of LCAA aneurysm with LSA aneurysm and coarctation [10] and Imai et al reported reconstruction with interposition graft of LCAA with coarctation [11]. Hirao et al reported LCAA aneurysm which had been thought to be a mediastinal tumour [12], and Higuchi employed left thoracotomy and partial cardiopulmonary bypass through descending aorta and IVC to repair LCAA aneurysm just distal to LCCA with aberrant and tortuous LSA [13]. …”
Section: Discussionmentioning
confidence: 99%